Changes in health behaviour of medical students during and after the COVID-19 pandemic—focus on physical activity, screen time, sleep duration, unhealthy foods, alcohol, and tobacco - Lukas Liebig; Willy Gräfe; Hendrik Berth; Béla Birkás; Nora Faubl; Erika Zelko; Erika Balogh; Henna Riemenschneider (Frontiers in Public Health)
IntroductionThe COVID-19 pandemic and the preventive measures led to a change in the health behaviour among the population. Medical students were particularly affected by this. Previous studies primarily focused on few health behaviours, were mostly conducted in 2020–2021, and did not assess the persistence of these behaviours post-pandemic.MethodsA combined cross-sectional and longitudinal approach were applied to examine changes in physical activity, screen time, sleep duration and consumption of unhealthy foods, alcohol and of tobacco. Data from Medical Students at the Technical University of Dresden were collected online as part of the multicenter study “Medical Student Health Survey” in 2020 and 2022. Descriptive and inferential statistical methods were applied.ResultsMedical students (N = 575) reported reduced physical activity and increased screen time due to the COVID-19 pandemic, citing lockdown and changed habits as main reasons. Longitudinal analysis of medical students (N = 66) between 2020 and 2022 revealed increased physical activity (p = 0.018) and decreased unhealthy food consumption (p = 0.009) after the end of the pandemic. Screen time, sleep duration and consumption of alcohol and of tobacco products remained unchanged. Changes in health behaviours were not intercorrelated.DiscussionThe COVID-19 pandemic led to change in health behaviour of medical students. However, intra-pandemic changes differing from pre-post pandemic changes and interindividual variations in health behaviour change were found. The rise in physical activity, the decreased consumption of unhealthy foods, and the low tobacco use reflect a health-aware cohort. The findings should inform the development of future preventive measures and further research is needed to understand the sustainability and broader impact of these health behaviour changes.